Moral distress and intention to leave: A comparison of adult and paediatric nurses by hospital setting. (October 2016) - Dyo, Melissa; Kalowes, Peggy; Devries, Jessica
Summary: Objectives: To assess moral distress intensity and frequency in adult/paediatric nurses in critical care and non-critical care units; and explore relationships of nurse characteristics and moral distress with intention to leave. Methods/setting: A descriptive, correlational design was used to administer an online survey using the Moral Distress Scale to nurses across multiple settings. Main outcome measures: Intensity and frequency of moral distress and intention to leave current position. Results: The survey response rate was 43% ( n = 426/1000). Critical care nurses had the highest levels of moral distress intensity and frequency, compared to non-critical care specialties ( M = 2.5 ± 0.19, p = 0.005 for intensity and M = 1.6 ± 0.11, p < 0.001 for frequency). Moral distress frequency showed a positive relationship with intention to leave a position of employment. Each unit increase in moral distress frequency doubled the odds of intention to leave when adjusting for age, gender, ethnicity and specialty area ( p = 0.003). Hispanic nurses had significantly higher levels of moral distress intensity ( p = 0.01). Conclusion: Moral distress is a complex phenomenon requiring further study, particularly with regard to the role of ethnic and cultural differences on perceptions of moral distress.